2022
DOI: 10.1073/pnas.2202371119
|View full text |Cite
|
Sign up to set email alerts
|

Protective anti-gB neutralizing antibodies targeting two vulnerable sites for EBV-cell membrane fusion

Abstract: Epstein-Barr virus (EBV) infects more than 90% of the world’s adult population and accounts for a significant cancer burden of epithelial and B cell origins. Glycoprotein B (gB) is the primary fusogen essential for EBV entry into host cells. Here, we isolated two EBV gB-specific neutralizing antibodies, 3A3 and 3A5; both effectively neutralized the dual-tropic EBV infection of B and epithelial cells. In humanized mice, both antibodies showed effective protection from EBV-induced lymphoproliferative disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 47 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…The architecture of PM biosensor is optimized in combination with the nanofabrication (Figures S5 and S6), optical measurement, and simulation. It consists of the vertically separate gold nanoholes and nanodisks with an orthogonal lattice on a silicon substrate, as shown in Figure D and Figure S9. The measured reflectance spectrum under normal light incidence demonstrates 4 distinct resonance dips in Figure A, which correspond to 4 specific plasmonic modes named as M1, M2, M3, and M4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of PM biosensor is optimized in combination with the nanofabrication (Figures S5 and S6), optical measurement, and simulation. It consists of the vertically separate gold nanoholes and nanodisks with an orthogonal lattice on a silicon substrate, as shown in Figure D and Figure S9. The measured reflectance spectrum under normal light incidence demonstrates 4 distinct resonance dips in Figure A, which correspond to 4 specific plasmonic modes named as M1, M2, M3, and M4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The two antibodies were identified to target and neutralize EBV-infected B cells and epithelial cells. These studies indicate that accurate localization of gB T cell epitopes is beneficial to the development of gB subunit vaccines and immune surveillance and that gB D-II and D-IV are promising targets for the development of EBV vaccines ( 58 , 80 ).…”
Section: Ebv-­directed Vaccinationmentioning
confidence: 95%
“…Functional analysis revealed that the binding affinity to gB and epithelial neutralizing activity of 3A3 and 3A5 were equivalent to AMMO5 in vitro. While 3A3 and 3A5 performed 10‐fold better than AMMO5 in B cell neutralization, they performed slightly more potent than AMMO5 in humanized mice model 93 . Structural analysis indicated that 3A3 blocked gB binding to its epithelial receptor NRP1, whereas 3A5 hindered gB conformational change from pre‐ to poststate.…”
Section: Ebv Antibodies As Antiviral Agents For Infection and Its Ass...mentioning
confidence: 99%